Experiential Marketing terhadap Minat Beli Ulang Konsumen - Dwi Oktavia Nirmalasari; Feti Fatimah; Wenny Murtalining Tyas (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to empirically examine the effect of experiential marketing on repurchase interest in sakera noodles at the Lake Toba branch of Jember. The independent variables examined in this study are sense, feel, think, act and relate, while the dependent variable is consumer repurchase interest. This research method is descriptive quantitative. Determination of the sample is done by using purposive sampling technique. The data analysis technique used multiple linear regression analysis, using SPSS statistics for window.26. The results showed that the results of the t-test carried out resulted in, a) the sense of repurchasing interest has a significance level of 0.000 and a positive regression coefficient of 0.236; b) the feel variable towards repurchase intention has a significance level value of 0.007 and a positive regression coefficient of 0.216; c) the think variable on repurchase interest has a significance level of 0.024 and a positive regression coefficient of 0.276; d) the act variable on repurchase interest has a significance level value of 0.000 and a positive regression coefficient of 0.449; e) the variable relates to repurchase interest has a significance level of 0.002 and a positive regression coefficient of 0.236. In conclusion, sense, feel, think, act and relate have a positive and significant influence on repurchase intention. Keywords: Act, Feel, Repurchase Interest, Relate, Sense, Think